Antiphospholipid antibody associated thrombosis in juvenile chronic arthritis. Issue 11 (November 1992) - Caporali, R; Ravelli, A; Ramenghi, B; Montecucco, C; Martini, A
Abstract : A child with systemic onset juvenile chronic arthritis (JCA) who developed a bilateral femuropopliteal vein thrombosis after plaster immobilisation following a tibial fracture is described. When the thrombosis was diagnosed, antiphospholipid antibodies detected either as lupus anticoagulant and anticardiolipin antibodies were found. This suggests that short term prophylatic antithrombotic treatment should be considered in antiphospholipid antibody positive JCA patients who require immobilisation after fractures of demineralised bones.